Complete Cephalic Migration of Subduroperitoneal Shunt System - Valdez Serra, Cristian; Sosa, Fidel; Rodríguez, Facundo; Bartuluchi, Marcelo (Revista Argentina de Neurocirugía, 2024)
Background: arachnoid cysts are defined as space-occupying lesions containing cerebrospinal fluid (CSF), which can be located anywhere in the nervous system where arachnoid cells are present. Fenestration surgery of arachnoid cysts may evolve with a subdural hygroma, requiring a subduroperitoneal shunt. Complete cephalic migration of a CSF shunt system is an extremely rare complication, with few cases reported in medical literature.Objectives: to describe and analyze the complication of complete cephalad migration of a CSF shunt system through a clinical case study.Case description: patient operated on for an arachnoid cyst who developed postoperative bilateral subdural hygromas requiring placement of a subduroperitoneal shunt. Postoperatively, the patient experienced complete cephalic migration of the shunt.Surgery: replacement of the entire system, using a programmable valve at its lowest pressure and securing it securely.Conclusion: this event highlights the importance of taking adequate precautions during the installation of the subduroperitoneal shunt to minimize the risk of cephalic migration. Although it is an infrequent complication, its possibility underscores the need to follow strict protocols and to be alert to early signs of migration to intervene in a timely manner.
Keywords: Arachnoid cyst; Subdural effusion; Subdural migration; Subduroperitoneal shunt